PROBLEMS OF TRANSLATING NAVOY'S LYRICS INTO FOREIGN LANGUAGES - Shermamatova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article talks about the translations of Alisher Navoi's ghazals and rubai into English by Uzbek and foreign translators. Their achievements and shortcomings are thoroughly analyzed. Some suggestions and recommendations were given and relevant conclusions were drawn